ANALISIS KESALAHAN DALAM MENYELESAIKAN SOAL PROBLEM SOLVING PADA OUTDOOR LEARNING MATHEMATICS DENGAN BANTUAN APLIKASI MATCH CITY MAP - Hasinatul Iman; Prima Cristi Crismono; Mely Pitasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the errors made by students of the Islamic Elementary School Teacher Education Program (PGMI) in solving mathematical problem-solving tasks through outdoor learning assisted by the match city map application. The research employed a descriptive qualitative approach focusing on error analysis to identify the types, patterns, and causes of students’ errors. The subjects consisted of three students selected purposively based on high, medium, and low mathematical abilities. Data were collected through problem-solving tests, interviews, participatory observations, and documentation of students’ work. The results reveal three main types of errors: conceptual, procedural, and presentation errors. High ability students mostly made procedural and presentation mistakes: medium ability students showed inconsistencies in unit handling and calculation accuracy while low ability students exhibited fundamental conceptual misunderstandings. The factors contributing to these errors include insufficient understanding of mathematical concepts, procedural difficulties, limited ability to connect problems with real contexts, inaccuracy in notation, and lack of effective problem-solving strategies. These findings highlight importance of differentiated instructional approaches and the integration of digital, context based media to enhance the problem-solving skills of future Islamic elementary school teachers.